Bestial Traces Race, Sexuality, Animality - Peterson, Christopher (Fordham University Press, 2022)
On February 18th, 2009, Sean Delonas published a controversial cartoon in the New York Post depicting two policemen shooting and killing a monkey with the caption: "They'll have to find someone else to write the next stimulus bill." On the adjoining page was a photo of President Barack Obama signing this very piece of legislation into law. Although public debate over the cartoon has centered entirely on its potentially racist overtones, we might ask from a Darwinian perspective how the stereotype of the black ape works to disavow a universally shared human apehood. How might we comprehend animality in non-pejorative terms? Whereas in contemporary race and sexuality studies the topic of animality emerges almost exclusively in order to index the dehumanization that makes discrimination possible, Bestial Traces argues that a more fundamental disavowal of human animality conditions the bestialization of racial and sexual minorities.